(3YeGO GdYed hGdYGUe ef GdNWG hGdRdds - (3CHh eMeO, cGXe Hf TajYs ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdbGOQ GdaYGd (B... (3deG cGf CaVd eG jJbQH efg Edi QH GdYGdejf HYO GdeYQaI GdYed eY GdYde HeSGFd GdOjfs
(3BNQgG (B:s
(3BNQgG(B: (3hdYOe eWGHbI GdNHQjf Ydi eG eQ ajWQMGf Ch jMedGf Ydi GdJbjI hEf cGf GdbGFd HeVehfgeG bdjdG ef GdYGeI hHg UQM HYV GdCLdI hHMeO Gddg XgQs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis